G523(P) Can we improve our lac service with child-focused initiatives – yes we can!. (May 2019) - Stephenson, RL; Chahal, J; Teebay, L; Hollywood, J
Abstract : Aims: To demonstrate that it is possible to improve the Looked after children (LAC) service through quality improvements projects. Methods: Two departmental audits were performed looking at: Quality and content of Initial Health assessment (IHA) reports Safeguarding assessments for children who progress to adoption Results: Conclusion: We have shown that we can improve the quality of LAC assessment, listen to the voice of the child and show commitment to engaging the CYP as key to the process. The result is a more cost effective service that empowers CYP.